'FIFA 11 for Health' for Europe. II: effect on health markers and physical fitness in Danish schoolchildren aged 10–12 years. Issue 22 (29th April 2016) - Ørntoft, Christina; Fuller, Colin W; Larsen, Malte Nejst; Bangsbo, Jens; Dvorak, Jiri; Krustrup, Peter
Abstract : Objectives: To evaluate whether a modified 'FIFA 11 for Health' programme for non-communicable diseases had effects on body composition, blood pressure and physical fitness of Danish schoolchildren aged 10–12 years. Design: A cluster-randomised controlled study with 7 intervention and 2 control schools. Participants: 546 Danish 5th grade municipal schoolchildren allocated to an intervention group (IG; n=402: 11.1±0.4 (±SD) years, 150.1±7.0 cm, 41.3±8.4 kg) and a control group (CG; n=144: 11.0±0.5 years, 151.2±7.8 cm, 41.3±9.0 kg). Intervention: As part of the physical education (PE) curriculum, IG carried out 2 weekly 45 min 'FIFA 11 for Health' sessions focusing on health issues, football skills and 3v3 games. CG continued regular school PE activities. Measurements of body composition, blood pressure at rest, Yo-Yo intermittent recovery level 1 children's test (YYIR1C), balance, jump and sprint performance were performed before and after the 11-week study period. Results: During the 11-week study period, systolic blood pressure (−3.5 vs 0.9 mm Hg), mean arterial blood pressure (−1.9 vs 0.4 mm Hg), body mass index (−0.02 vs 0.13 kg/m 2 ) and body fat percentage (−0.83% vs −0.04%) decreased more (p<0.05) in IG than in CG. Within-group improvements (p<0.05) were observed in IG for 20 m sprint (4.09±0.29 to 4.06±0.28 s) and YYIR1C performance (852±464 to 896±517 m), but these changes were not significantly different from CG, and balance or jump performance remained unchanged in both groups. Conclusions: The modified 'FIFA 11 for Health' programme has beneficial effects on body composition and blood pressure for Danish schoolchildren aged 10–12 years, thereby providing evidence that this football-based health education programme can directly impact participants' cardiovascular health profile.